The use of treated effluent for agricultural irrigation in the Bottelary River area: Effluent quality, farmers perception and potential extent - Rui, Li (University of the Western Cape, 2013)
Magister Scientiae - MSc === The Bottelary River area is located in a Mediterranean climate region, where the agricultural sector plays an important role. During the dry summer season, there is not enough precipitation to meet the agricultural irrigation requirements. Some farmers extract river water which is practically the final treated effluent from the Scottsdene Wastewater Treatment Works to irrigate crops. This research investigated the use of treated effluent for agricultural irrigation in this area, particularly focused on the effluent quality, farmers perception, and the potential extent. === South Africa